MOLECULAR PATHOPHYSIOLOGY OF THROMBOTIC STATES AND THEIR IMPACT TO LABORATORY DIAGNOSTICS - Slavik, Ludek; Krcova, Vera; Hlusi, Antonin; Prochazkova, Jana; Prochazka, Martin; Ulehlova, Jana; Indrak, Karel (Biomedical papers, 2009)
BACKGROUND: Molecular genetic methods were implemented in the detection of thrombophilic disorders in the 1990's with the discovery of coagulation inhibitors antithrombin III (AT III), protein C (PC) and S (PS). The discovery of the molecular cause of activated protein C (APC) resistance by Bertina in 1994 greatly expanded their utilization.METHODS AND RESULTS: Currently, a broad group of molecular genetic markers with a clearly demonstrated risk of thrombophilia are used - mutation of FV Leiden 506R/Q, mutation of prothrombin (F II) 20210G/A, mutation of methylenetetrahydrofolate reductase (MTHFR) 677C/T in homozygous form, mutation of plasminogen activator inhibitor (PAI-1) 4G/5G, mutations of single coagulation inhibitors as well as a number of polymorphisms with controversial thrombophilic risk such as F XIII Val34Leu, platelet glycoproteins, endothelial protein C receptor and thrombomodulin. Another area utilizing molecular genetic methods is research of the pathophysiology of individual coagulation processes. To date, the greatest advances in regard to APC resistance have been achieved here. Although the molecular cause of APC resistance was clearly demonstrated in the 1990's, its clinical variability has not yet been fully explained. The same is true for the second most widespread mutation, prothrombin gene mutation, where only the latest research has hinted at a possible mechanism of expression of the genetic changes in the actual coagulation process.CONCLUSIONS: The future of molecular genetic methods is in achieving a complex understanding of the pathophysiology of thrombophilia and not only in its utilization as a method for detecting many polymorphisms with a very low risk of thrombosis.
Keywords: Thrombophilia/Genetic causes of thrombophilia/FV Leiden